1929 Mo. Laws 170, Crimes and Punishment, Prohibiting the Sale, Delivery, Transportation, Possession, or Control of Machine Rifles, Machine Guns and Sub-machine Guns, and Providing Penalty for Violation of Law, §§ 1-2 - (:unkn) unknown (General Publisher, 1929)
Prohibited selling, delivering, transporting, and possessing a machine gun. Punishable by imprisonment of 2-30 years and/or fine up to $5,000.
--
Keywords: MACHINE GUN RESTRICTION